Meaning in life and adjustment to daily stressors. Issue 4 (4th July 2017) - Park, Jina; Baumeister, Roy F.
Abstract: People perceive their life as meaningful when they find coherence in the environment. Given that meaning of life is tied to making sense of life events, people who lack meaning would be more threatened by stressful life events than those with a strong sense of meaning in life. Four studies demonstrated links between perceptions of life's meaningfulness and perceived levels of stress. In Study 1, participants with lower levels of meaning in life reported greater stress than those who reported higher meaning in life. In Study 2 and Study 3, participants whose meaning in life had been threatened experienced greater stress than those whose meaning in life had been left intact. In Study 4, anticipation of future stress caused participants to rate themselves higher on the quest for meaning in life. These findings suggest that perceiving life as meaningful functions as a buffer against stressors.